Regulations of LINC0196/miR-584-5p/miR-34a-5p/TRIM59 on Progression of Pediatric Neuroblastoma: LINC0196/miR-584-5p/miR-34a-5p/TRIM59 and Pediatric Neuroblastoma - Xie, Pengfei; Wang, Zhen; Chen, Xia; Han, Ying; Yang, Mei; Ye, Zhuang (Cellular and Molecular Biology, 2022)
This work was to study the regulatory mechanism of large intergenic non-coding RNA 0196 (LINC0196), miR-584-5p, miR-34a-5p, and tripartite motif 59 (TRIM59) on neuroblastoma. The interaction among the four was analyzed to provide a research basis for the clinical treatment of neuroblastoma at the molecular level. The human neuroblastoma SK-N-SH cells were collected and cultured. According to the transfection methods, the cells were divided into control group (without any treatment), si-LINC0196 group (si-LINC0196 transfection), si-LINC0196-NC group (si-LINC0196 vector transfection), miR-584-5p group (miR-584-5p mimic transfection), miR-584-5p-NC group (miR-584-5p inhibitor transfection), miR-34a-5p group (miR-34a-5p mimic transfection), and miR-34a-5p-NC group (miR-34a-5p inhibitor transfection). The proliferation, migration, and apoptosis of SK-N-SH cells in each group were compared. The effects of LINC0196, miR-584-5p, miR-34a-5p, and TRIM59 were evaluated. The expressions of LINC0196 and TRIM59 in SK-N-SH cells in si-LINC0196, miR-584-5p, and miR-34a-5p groups were up-regulated. miR-584-5p and miR-34a-5p in si-LINC0196-NC, miR-584-5p-NC, and miR-34a-5p-NC groups decreased significantly (P < 0.05). The proliferation rate, migration rate, and invasiveness of SK-N-SH cells in miR-584-5p and miR-34a-5p groups were lower than those in si-LINC0196-NC, miR-584-5p-NC, and miR-34a-5p-NC groups, while the apoptosis rate increased (P < 0.05). After miR-584-5p and miR-34a-5p transfections, the relative activities of WT-LINC0196 and WT-TRIM59 dual luciferase were greatly inhibited (P < 0.05). LINC0196 could regulate TRIM59 by regulating miR-584-5p and miR-34a-5p, thereby indirectly regulating cell proliferation, apoptosis, migration, and invasion of SK-N-SH cells.